If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 8 = -1x + -4 Reorder the terms: 8 + 2x = -1x + -4 Reorder the terms: 8 + 2x = -4 + -1x Solving 8 + 2x = -4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 8 + 2x + x = -4 + -1x + x Combine like terms: 2x + x = 3x 8 + 3x = -4 + -1x + x Combine like terms: -1x + x = 0 8 + 3x = -4 + 0 8 + 3x = -4 Add '-8' to each side of the equation. 8 + -8 + 3x = -4 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = -4 + -8 3x = -4 + -8 Combine like terms: -4 + -8 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 4x^2-6x+57=19 | | 7x-y=8 | | 71a+18c=11 | | 4x+8=6x-10 | | 4x+3=13+2x | | x^2-16x+64+6x^8-48x^7=0 | | 2w+2(2w-4)=76 | | 8x-2=4x-10 | | 6x+7=3x-2 | | x^2+12x-2=0 | | 5(3z-1)-3(z+2)=2(2+1) | | 6x+2=4x-4 | | 44a-16a-5(a+6)-9=6 | | 5x+5(4)=20 | | -6(x+11)+299=21+14 | | 12+15x= | | 2x+15=59 | | -6(x+9)+368=25+19 | | x+15=59 | | x-15=59 | | -18x-5=13 | | t-16=28 | | 5(2.5-x)=7.5x | | 5(2.5-x)=7.5 | | -3x+x+7=0 | | 2(r-4)=5r-2 | | -6=2x+2 | | 4(5x-1)-5(z+8)=11(z+1) | | 3d+4=2+2d | | -31=4x-7 | | 3a+2b+4a+b= | | 95-7x=29x+19 |